(untitled) (Bangladesh Journal of Botany, 2015)
Thirty five wild rice germplasm accessions collected from natural habitat of Eastern Indo-Gangetic region of India were evaluated to estimate their extent of genetic variability, agro-morphological divergence and relationship among themselves for 14 traits. The accessions showed significant genotypic coefficient of variation for all traits analyzed. The accessions were clustered into six groups, the cluster III contained the highest 12 accessions, and clusters I and IV comprised 11 and 7 accessions, respectively; while cluster II and VI have two accessions each, and clusters V was monogenotypic. The maximum intra-cluster distance was observed in cluster VI followed by clusters IV and II while in inter-cluster distance was observed between clusters V and VI followed by clusters II and V indicates wider genetic diversity between germplasm accessions. High heritability coupled with high genetic advance as per cent of mean was found in the traits filled grains per panicle, total number of grains per panicle and grain yield per plant. The result suggested that these accessions are valuable resource and can be utilized for yield and yield traits besides disease and pest. Therefore, these accessions should be conserved to utilize in transgressive segregation breeding programme of cultivated indica rice. DOI: http://dx.doi.org/10.3329/bjb.v43i3.21607 Bangladesh J. Bot. 43(3): 337-344, 2014 (December)